2004
DOI: 10.1177/1077559504266998
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Children in Kin Versus Nonkin Foster Care: Perceived Costs and Benefits to Caregivers

Abstract: This study uses social exchange theory as a framework for examining 102 kin and 157 nonkin foster parents' perceptions of their foster children, their relationships with them, and their own functioning. The authors argue that these perceptions reflect perceived costs and benefits of parenting these children, which may influence their investment in them. All children in the study were referred to Parent-Child Interaction Therapy (PCIT) for treatment of the children's behavior problems, participating with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 21 publications
2
52
1
Order By: Relevance
“…One issue of concern identified by Timmer et al 656 (not for the first time) is that kin foster carers lack much-needed support in managing the challenging behaviour of the children whom they are fostering.…”
Section: Summary: Acceptability Of Relationship-based Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…One issue of concern identified by Timmer et al 656 (not for the first time) is that kin foster carers lack much-needed support in managing the challenging behaviour of the children whom they are fostering.…”
Section: Summary: Acceptability Of Relationship-based Interventionsmentioning
confidence: 99%
“…The rationale for the study 656 was that such perceptions might impact on the investment that foster carers make in their foster children, all of whom had been referred to PCIT on account of their behaviour problems.…”
Section: Study Design and Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Examining findings from nine studies from 1994 to 2004, Winokur et al (2009) concluded that children in non-relative foster care were more likely to receive mental health services than children placed in kinship foster care, though it is unclear whether these differences in mental health utilization were due to underlying differential need between children in kin and non-kin care, or differences in knowledge and/or access to care among kin and non-kin providers. One explanation for differences in receipt of formal mental health treatment draws from evidence that the same child behavior may be interpreted or reported differently, based on the caregiver relationship to the child (Gebel, 1996;Rosenthal & Curiel, 2006;Timmer, Sedlar, & Urquiza, 2004;), and that kin may provide positively skewed assessments of the behavior of children in their care (Barth, 2008;Shore, Sim, Le Prohn, & Keller, 2002), which might result in children receiving less formal treatment for their behavior because caregivers do not perceive it as sufficiently problematic or warranting intervention (Daly & Perry, 2011).…”
Section: The Potential Benefits and Challenges Of Kinship Foster Carementioning
confidence: 99%